SOCIAL MEDIA AND CYBERBULLYING: LEGAL AND ETHICAL PERSPECTIVES IN COMMUNICATION - Khoirunnisa, Khoirunnisa; Jubaidi, Didi (Pojok Publisher, 2025)
Cyberbullying is intimidation conducted through social media, emerging with the rise of technology and social media use. This phenomenon has severe psychological impacts on victims. This study examines cyberbullying from the perspectives of law and communication ethics, recognizing that current regulations often inadequately address such cases. The ethical use of social media is essential, not only to uphold dignity but also to prevent negative effects and legal complications. This research analyzes the role of social media in cyberbullying and the legal and ethical aspects of its regulation in Indonesia. Employing a normative juridical method with a legislative approach, the study uses secondary data from literature. Findings reveal that cyberbullying stems from insufficient ethical awareness in social media use. Addressing this requires stronger, specific regulations to improve case management, enhance victim protection, and foster a safer, more respectful online environment.